Selective Lanthanide‐Organic Catalyzed Depolymerization of Nylon‐6 to ϵ‐Caprolactam. Issue 4 (16th December 2022) - Wursthorn, Lukas; Beckett, Kristen; Rothbaum, Jacob O.; Cywar, Robin M.; Lincoln, Clarissa; Kratish, Yosi; Marks, Tobin J.
Abstract: Nylon‐6 is selectively depolymerized to the parent monomer ϵ‐caprolactam by the readily accessible and commercially available lanthanide trisamido catalysts Ln(N(TMS)2 )3 (Ln=lanthanide). The depolymerization process is solvent‐free, near quantitative, highly selective, and operates at the lowest Nylon‐6 to ϵ‐caprolactam depolymerization temperature reported to date. The catalytic activity of the different lanthanide trisamides scales with the Ln 3+ ionic radius, and this process is effective with post‐consumer Nylon‐6 as well as with Nylon‐6+polyethylene, polypropylene or polyethylene terephthalate mixtures. Experimental kinetic data and theoretical (DFT) mechanistic analyses suggest initial deprotonation of a Nylon terminal amido N−H bond, which covalently binds the catalyst to the polymer, followed by a chain‐end back‐biting process in which ϵ‐caprolactam units are sequentially extruded from the chain end. Abstract : Commercial and post‐consumer Nylon‐6 are selectively recycled to the ϵ‐caprolactam monomer in high yields by readily accessible lanthanide tris(amide) catalysts in a solvent‐free process. Catalytic activity scales with the lanthanide ionic radius. A chain‐end backbiting mechanism is proposed from experimental and theoretical analyses.